2008
DOI: 10.1097/cej.0b013e3282f75f3e
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity determines association of p53Arg72Pro alleles with cervical cancer in China

Abstract: Minority Uigur women residing in Xinjiang, in the northwest of China, have a high incidence of cervical carcinoma (CC; 527/100 000) and are often diagnosed young. We favor the hypothesis that Uigur women may carry different genetic factor(s) making them more susceptible to CC than majority Han (Chinese) women living in the same region. Using PCR-restriction fragment length polymorphism, we investigated associations of a p53Arg72Pro polymorphism with CC in Uigur women compared with those in Han women. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…S1). Two publications reported results for 2 independent populations (18,19). These were assessed as 2 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Two publications reported results for 2 independent populations (18,19). These were assessed as 2 separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…According to the inclusion criteria, 28 studies (Minaguchi et al, 1998;Ngan et al, 1999;Baek et al, 2000;Kim et al, 2000;Kim et al, 2001;Yang et al, 2001;Bhattacharya et al, 2002;Kawamata et al, 2002;Nagpal et al, 2002;Saranath et al, 2002;Xi et al, 2002;Cho et al, 2003;Katiyar et al, 2003;Cho et al, 2004;Lee et al, 2004;Li et al, 2004;Wang et al, 2004;Wu et al, 2004;Yoshimitsu et al, 2004;Masatsugu et al, 2005;Mitra et Yao et al, 2008;Zheng et al, 2008;Zhou et al, 2009) were included and 103 were excluded in this meta-analysis. The flow chart of study selection is shown in Figure 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…The Xinjiang region of China shows a high incidence of cervical cancer, and Uyghur women in particular exhibit a significantly high risk of cervical cancer. The prevalence of cervical cancer is significantly higher in Uyghur women than that in any other ethnic group; the incidence of cervical cancer among Uyghur women in Xinjiang has been reported to be 459/100,000–527/100,000, which is significantly higher than the incidence in any other region of China [ 4 – 6 ]. Multiple factors, such as human papillomavirus (HPV) infection, marriage and childbearing, contribute to the high incidence of cervical cancer among this population [ 7 ].…”
Section: Introductionmentioning
confidence: 99%